(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
Throughout history, the treatment of patients has had many approaches. At first the treatment was performed by doctors who practiced surgery. Later there was a specialization of the professional who performed surgical procedures. In the Middle Age, there was a figure who was the barber surgeon who treated the sick without great knowledge or technical training. Over the centuries, these barbers who coexisted with more scientific surgeons disappeared, especially when a training system for the surgical professional was implemented, until the current moment that the surgeon has a clear differentiation and great specialization